Instrument Development For Measuring Factors Influencing Fog Computing Adoption Based On Quality Of Results (Qor): Content Validity - Nur Hamezah Abdul Malic, Tengku Adil Tengku Izhar, Mohd Razilan Abdul Kadir (International Journal of Advanced Science and Technology, 2020)
Big data analysis on data transmitted from the ever increases devices is directly or indirectly likely to influence the adoption of fog computing. Fog computing was introduced to cater the ever increasing demand Internet of Things that generate huge amounts of data. The objective of this paper is to present the process of determining the content validity of instrument item in order to conduct a study in determining factors influencing fog computing adoption based on quality of results (QoR) for heterogeneous data analysis. Selection or generation of items were adopt and adapt from assessment instruments of other studies. Items reviewed by a panel of experts in term of the relevancy and representativeness. The Item Content Validity Item (I-CVI) and Scale Content Validity Index (S-CVI) computed. The finding from the assessment confirmed that the instrument is relevant with few item modifications is required.